2020
DOI: 10.18632/aging.103199
|View full text |Cite
|
Sign up to set email alerts
|

Immune profiling reveals prognostic genes in high-grade serous ovarian cancer

Abstract: High-grade serous ovarian cancer (HGSOC) is a heterogeneous disease with diverse clinical outcomes, highlighting a need for prognostic biomarker identification. Here, we combined tumor microenvironment (TME) scores with HGSOC characteristics to identify immune-related prognostic genes through analysis of gene expression profiles and clinical patient data from The Cancer Genome Atlas and the International Cancer Genome Consortium public cohorts. We found that high TME scores (TMEscores) based on the fractions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Mounting evidence demonstrated that IRGs is closely related to hepatocellular carcinoma [ 22 ], gastric cancer [ 23 ], and ovarian cancer [ 24 ]. However, there is still a lack of comprehensive analyses of IRGs in psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence demonstrated that IRGs is closely related to hepatocellular carcinoma [ 22 ], gastric cancer [ 23 ], and ovarian cancer [ 24 ]. However, there is still a lack of comprehensive analyses of IRGs in psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian cancer, studies have begun to explore the relationship between immune composition, immune-related genes, and clinical outcomes. Several studies have used computational analysis of tumors with publicly available gene expression data to report relationships between immune cell subsets or gene expression and prognosis (10)(11)(12)(13)). Yet other studies have employed immunohistochemical approaches to establish a relationship between intra-epithelial T cells and other immune cell subsets and survival (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The role of tumor microenvironment in predicting clinical outcome and efficacy was gradually recognized. Researchers were trying to find reliable immune-related prognostic genes in ovarian cancer, including TAP1 (Liu et al, 2020;Wu et al, 2020;Huo et al, 2021) and CXCL13 (Liu et al, 2020;Wu et al, 2020;Li et al, 2021). The results were based on screening for differentially expressed genes between high and low abundance immune subtypes (Li et al, 2021), ovarian cancer and normal tissues (Liu et al, 2020), high and low Tumor Mutational Burden (TMB) samples (Huo et al, 2021), high and low tumor microenvironment scores (Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers were trying to find reliable immune-related prognostic genes in ovarian cancer, including TAP1 (Liu et al, 2020;Wu et al, 2020;Huo et al, 2021) and CXCL13 (Liu et al, 2020;Wu et al, 2020;Li et al, 2021). The results were based on screening for differentially expressed genes between high and low abundance immune subtypes (Li et al, 2021), ovarian cancer and normal tissues (Liu et al, 2020), high and low Tumor Mutational Burden (TMB) samples (Huo et al, 2021), high and low tumor microenvironment scores (Wu et al, 2020). However, TAP1 and CXCL13 as main prognostic markers were primarily carried out using a univariate Cox model (Wu et al, 2020), without considering the influence of other genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation